The SUS principles and the educative practices of nurses in the Family Health Program. A qualitative study. - Vanessa Almeida Ferreira; Sonia Acioli; Ariádina Heringer; Ana Luisa Silva Barros (Online Brazilian Journal of Nursing, 2006)
This article discusses the results of a research that aimed to identify how the nurses engaged in the Family Health Program of the community of Complexo do Alemão, in the city of Rio de Janeiro, recognize the SUS principles in the context of their educative practices. It is a qualitative study, adopting the dialectical approach as its methodological framework, and has used interviews and semi-structured observation for data collection. By accomplishing this study, we have sought to contribute for nurses’ reflection on the importance of innovative and transformative educational practices that promote the incorporation of the SUS principles.